The effect of transverse friction massage on pain and quality of life in women with chronic pelvic pain: A quasi-experimental study - Ersin, Aybüke; Tarhan, Fatih; Başol, Gülfem; Şakul, Bayram Ufuk; Algun, Zeliha Candan (Mark Allen Group, 2023)
Background/Aims Chronic pelvic pain is defined as pain located to the pelvis or lower abdominal region, lasting for at least 6 months, and not associated with menstruation, coitus or pregnancy. The aim of this study was to investigate the feasibility and effectiveness of transverse friction massage on pain and quality of life in women with chronic pelvic pain. Methods A total of 20 women participated in this study. Eight sessions of transverse friction massage were performed twice a week for 4 weeks, with each session lasting 30 minutes. Pelvic floor muscles (in terms of tenderness, trigger point, spasm and scar presence) were evaluated by digital palpation by an expert physiotherapist. The outcome measures used were the visual analogue scale, the 36-item Short Form-36 Survey and the Beck Depression Inventory. Participants were evaluated before treatment, at the end of the treatment, and 4 weeks after the end of the treatment. Results Participants' mean age was 49.7 +/- 0.31 years. There was a decrease in pain intensity and an increase in quality of life scores (P<0.001), but no statistically significant improvement in depression status at the end of the treatment (P>0.001). Four weeks after the end of the treatment, significant decreases in pain severity, quality of life and depression were observed (P<0.001). Conclusions Transverse friction massage is a feasible treatment option that can safely be used by physiotherapists to treat patients with chronic pelvic pain. It is inexpensive and can help to reduce pain and increase patients' quality of life. Randomised controlled trials are recommended to further confirm the findings from this study.
Keywords: Chronic Pelvic Pain; Muscle Tenderness; Pelvic Floor; Quality of Life; Transverse Friction Massage